Racial and ethnic differences in the health of older Americans - Martin, Linda G., 1947-; Soldo, Beth J.; National Research Council (U.S.). Committee on Population (Washington, D.C. : National Academy Press, 1997)
Older Americans, even the oldest, can now expect to live years longer than those who reached the same ages even a few decades ago. Although survival has improved for all racial and ethnic groups, strong differences persist, both in life expectancy and in the causes of disability and death at older ages. This volume examines trends in mortality rates and selected causes of disability (cardiovascular disease, dementia) for older people of different racial and ethnic groups.
The determinants of these trends and differences are also investigated, including differences in access to health care and experiences in early life, diet, health behaviors, genetic background, social class, wealth and income. Groups often neglected in analyses of national data, such as the elderly Hispanics and Asian Americans of different origin and immigrant generations, are compared. The volume provides understanding of research bearing on the health status and survival of the fastest-growing segment of the American population.
Racial and ethnic differences in mortality at older ages / Irma T. Elo and Samuel H. Preston -- Health and disability differences among racial and ethnic groups / Kenneth G. Manton and Eric Stallard -- Race, socioeconomic status, and health in late life / James P. Smith and Raynard S. Kington -- How health behaviors and the social environment contribute to health differences between Black and white older Americans / Lisa F. Berkman and Jewel M. Mullen -- Black-white differences in the use of medical care by the elderly : a contemporary analysis / José J. Escarce and Frank W. Puffer -- Are genetic factors involved in racial and ethnic differences in late-life health? / James V. Neel -- Differences in rates of dementia between ethno-racial groups / Barry Gurland [and others] -- Cardiovascular disease among elderly Asian Americans / Dwayne Reed and Katsukiko Yano -- Health status of Hispanic elderly / Kyriakos S. Markides [and others].
Revised versions of some of the papers originally presented at a workshop held Dec. 1994 in Washington.
Includes bibliographical references.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Minority older people -- Health and hygiene -- United States; Minority older people -- Diseases -- United States; Older people; Race; Ethnic groups; Aged; Health Status; Racial Groups; Socioeconomic Factors; Ethnicity; Aged, 80 and over; United States; Personnes âgées issues des minorités -- Santé et hygiène -- États-Unis.; Personnes âgées issues des minorités -- Maladies -- États-Unis.; Personnes âgées.; Race; Groupes ethniques; elderly; ethnic groups; race (group of people); MEDICAL -- Preventive Medicine; HEALTH & FITNESS -- Healthy Living; HEALTH & FITNESS -- Reference; HEALTH & FITNESS -- Holism; Race; Older people; Ethnic groups; United States; Gezondheid; Ouderen; Etnische minderheden; Electronic books; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings; Actes de congrès.